Use of Factor Analysis to Improve Questionnaire-Based Research Design (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Questionnaire-based research remains one of the most commonly used methods in social sciences, management, psychology, education, and health studies. However, the reliability and validity of the conclusions depend heavily on the quality of the questionnaire. Factor Analysis (FA), a multivariate statistical technique, provides a systematic approach to evaluate and refine questionnaires by identifying underlying latent constructs, reducing redundant items, and improving overall measurement accuracy. This article discusses the conceptual foundation of factor analysis, its methodological applications in questionnaire design, and practical guidelines for researchers to enhance instrument reliability and validity.